Developing a tactical irrigation and nitrogen fertilizer management strategy for winter wheat through drip irrigation - Zain, Muhammad; Si, Zhuanyun; Ma, Haijiao; Cheng, Minghan; Khan, Adam; Mehmood, Faisal; Duan, Aiwang; Sun, Chengming (Frontiers in Plant Science, 2023)
Introduction Agricultural activities in the North China Plain are often challenged by inadequate irrigation and nutrient supply. Inadequate and improper resource utilization may impose negative impacts on agricultural sustainability. To counteract the negative impacts, a deeper understanding of the different resource management strategies is an essential prerequisite to assess the resource saving potential of crops. Methods We explored plausible adaptation strategies including drip irrigation lateral spacings of 40 and 80 cm (hereafter referred to as LS40 and LS80, respectively), irrigating winter wheat after soil water consumption of 20 and 35 mm (hereafter represented as IS20 and IS35, respectively), and nitrogen fertilization scheme of a) applying 50% nitrogen as a basal dose and 50% as a top-dressing dose (NS50:50), b) 25% nitrogen as a basal dose and 75% as a topdressing dose (NS25:75), and c) no nitrogen application as a basal dose and 100% application as a top-dressing dose (NS0:100). Results and discussion The consecutive 2 years (2017–2018 and 2018–2019) of field study results show that growing winter wheat under LS40 enhanced the water use efficiency (WUE), grain yield, 1,000-grain weight, and number of grains per spike by 15.04%, 6.95%, 5.67%, and 21.59% during the 2017–2018 season, respectively. Additionally, the corresponding values during the 2018–2019 season were 12.70%, 7.17%, 2.66%, and 19.25%, respectively. Irrigation scheduling of IS35 treatment improved all the growth-related and yield parameters of winter wheat. Further, treating 25% nitrogen as a basal dose and application of 75% as a top-dressing dose positively influenced the winter wheat yield. While NS0:100 increased the plant height, leaf area index (LAI), and aboveground biomass as compared to the other application strategies, but high nitrogen was observed in deeper soil layers. Regarding soil environment, the lowest soil moisture and nitrate nitrogen contents were observed in LS80 during both growing seasons. Overall, coupling the IS35 with NS25:75 under 40-cm lateral spacing is a suitable choice for sustainable winter wheat production in theNorth China Plain. The results of our study may be helpful in advancing the knowledge of the farmer community for winter wheat production. The findings can also aid in advancing new insights among scientists working on soil water and nitrogen distribution in drip irrigation for better productivity.